PENERAPAN TEKNOLOGI AUTOCLAVE CERDAS UNTUK PEMBERDAYAAN MASYARAKAT PETANI JAMUR: STUDI KASUS DI PKT. SUBUR JAYA - Februariyanti, Herny; Sukur, Muji; Nurraharjo, Eddy; Nofiyanto, Erwin (Jurnal Abdi Insani, 2024)
The production of high-quality mushroom seeds is a crucial aspect in supporting the growth of the oyster mushroom industry in Indonesia. The demand for sterile and contamination-free seeds is increasing along with the growth of the mushroom farming sector in various regions. However, the main challenge faced by farmers is the limitation of efficient sterilization technology for growing media, which affects the quality of seedlings and mushroom production yields. The Community Partnership Empowerment (PKM) funded by the 2024 Kemenristek Dikti Grant focuses on enhancing the capacity and skills of mushroom farmers in Subur Jaya through the introduction and training in the use of smart autoclaves. The service method includes three main stages: (1) socialization to introduce smart autoclave technology to farmers; (2) training on the operation and maintenance of the smart autoclave; and (3) assistance in the application of technology over several cycles of mushroom seed production. The implementation of the smart autoclave not only enhances the knowledge and skills of the partners but also increases the number of mushroom farmers involved in PKT. Subur Jaya has grown and is no longer dependent on other regions for mushroom seed supplies. The smart autoclave technology that provides temperature and air pressure control according to production needs can reduce microbial growth, thereby minimizing harvest failures by up to 30%. The community service activity was successfully carried out as planned, and the implementation of a smart autoclave improved the quality of mushroom seedlings.